2013
DOI: 10.12681/mms.334
|View full text |Cite
|
Sign up to set email alerts
|

Is Posidonia oceanica regression a general feature in the Mediterranean Sea?

Abstract: Over the last few years, a widespread regression of Posidonia oceanica meadows has been noticed in the Mediterranean Sea. However, the magnitude of this decline is still debated. The objectives of this study are (i) to assess the spatio-temporal evolution of Posidonia oceanica around Cap Corse (Corsica) over time comparing available ancient maps (from 1960) with a new (2011) detailed map realized combining different techniques (aerial photographs, SSS, ROV, scuba diving); (ii) evaluate the reliability of ancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…The five Mediterranean seagrasses are subject to natural and anthropogenic pressures and even if the decline of meadows seems, in general, to be relatively limited (between 0 and 10 % throughout the 20th century; Gonzalez-Correa et al, 2007;Boudouresque et al, 2009), more significant rates of decline (up to 5-8 % per year) were locally observed in places that are subjected to strong anthropogenic pressures (Marbà et al, 1996) while meadows growing in pristine sites remain stable (Bonacorsi et al, 2013). Along the highly urbanised coasts of Liguria, Italy, extensive coastal development during the 1960s led to an estimated 30 % regression of P. oceanica meadows (Bianchi & Peirano, 1995;Peirano & Bianchi, 1997).…”
Section: Decline Of Mediterranean Seagrass Meadowsmentioning
confidence: 99%
“…The five Mediterranean seagrasses are subject to natural and anthropogenic pressures and even if the decline of meadows seems, in general, to be relatively limited (between 0 and 10 % throughout the 20th century; Gonzalez-Correa et al, 2007;Boudouresque et al, 2009), more significant rates of decline (up to 5-8 % per year) were locally observed in places that are subjected to strong anthropogenic pressures (Marbà et al, 1996) while meadows growing in pristine sites remain stable (Bonacorsi et al, 2013). Along the highly urbanised coasts of Liguria, Italy, extensive coastal development during the 1960s led to an estimated 30 % regression of P. oceanica meadows (Bianchi & Peirano, 1995;Peirano & Bianchi, 1997).…”
Section: Decline Of Mediterranean Seagrass Meadowsmentioning
confidence: 99%
“…Ten percent is the global decline (loss of area) generally accepted for P. oceanica over the last 100 years (Boudouresque et al, 2012) but a recent paper claims a reduction by 50% of the density or biomass within the Mediterranean over the last 20 years (Marb a et al, 2014a). Actually, the magnitude of the overall P. oceanica area loss over the last century ranges from 0 to 50 % depending on the author (Gonz alez-Correa et al, 2007;Boudouresque et al, 2009;Bonacorsi et al, 2013) but could reach 8% per year with possible functional extinction in 2059 according to others (Marb a et al, 1996;Jord a et al, 2012). The reality is difficult to assess because of a lack of reliable baseline data: quasi-absence of historical data, studies often only focusing on small spatial and temporal scales and/or using uncertain old maps (Montefalcone et al, 2013;Bonacorsi et al, 2013).…”
Section: Introduction Q1mentioning
confidence: 99%
“…Actually, the magnitude of the overall P. oceanica area loss over the last century ranges from 0 to 50 % depending on the author (Gonz alez-Correa et al, 2007;Boudouresque et al, 2009;Bonacorsi et al, 2013) but could reach 8% per year with possible functional extinction in 2059 according to others (Marb a et al, 1996;Jord a et al, 2012). The reality is difficult to assess because of a lack of reliable baseline data: quasi-absence of historical data, studies often only focusing on small spatial and temporal scales and/or using uncertain old maps (Montefalcone et al, 2013;Bonacorsi et al, 2013). These observed declines are mainly located near urban areas (Thomas et al, 2005;Boudouresque et al, 2012) and mostly associated with human activities even if they can sometimes be related to natural processes (e.g.…”
Section: Introduction Q1mentioning
confidence: 99%
“…However, in areas characterized by moderate anthropogenic pressures, P. oceanica seascapes have a relatively low percentage of patches that result from human impact. For example, in Corsica (France), patches resulting from anthropogenic impact comprise only a maximum 6% of the total seagrass area and no further significant regression has been recorded Bonacorsi et al, 2013).…”
Section: Available Literature On Posidonia Oceanica Seascape Ecologymentioning
confidence: 99%